Where I found you [large type] - St. Amant, Betsy (Magnolia Bay, 2026)
"Noah Hebert recently inherited the Blue Pirogue Inn--along with all its problems. He needs money to keep his beloved childhood home from being shut down by his family's longtime nemesis, Isaac Bergeron. So when Noah's lawyer approaches him about an additional segment of his late grandfather's will, it's just in the nick of time. But even from beyond the grave, his grandfather is up to his usual games. In order to receive the last portion of inheritance, Noah must follow the clues. But there's one condition . . . Magnolia Blossom Café manager Elisa Bergeron is shocked to discover an acquaintance from the local Puzzlers Club left her something in his will--and even more surprised to discover they are clues to a portion of his estate. When she learns she must work with Noah Hebert, a boy from her past, to solve the puzzle, she's torn. Growing up in the middle of a multi-generational feud between their families, she's been taught by her father, Isaac, that Heberts can't be trusted. When these two exes must work together to save their future, will love get a second chance or will the longstanding family feud claim another generation?"--